Synthesis and evaluation of inhibitors of cell wall biosynthesis in Mycobacterium tuberculosis - May, Terry J. (2016)
The emergence of drug-resistant strains of tuberculosis has led to a demand for the development of new antibiotics. One new target is the cell wall biosynthesis enzyme UDP-Galp mutase (UGM), which aids the formation of the bacteria’s characteristic mycolic acid cell wall. LQ10 and LQ6 were discovered through a library screen. The synthesis of LQ10 was achieved along with 4 analogues. Another class of compounds, 2-aminothiazoles, were produced. Thirteen of these compounds were produced and along with the LQ10 analogues, initially gave encouraging results in silico.